2019
DOI: 10.1785/0220190093
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Orientations of the S‐net Cabled Ocean‐Bottom Sensors

Abstract: The Seafloor Observation Network for Earthquakes and Tsunamis along the Japan Trench (S‐net) is a novel cabled ocean‐bottom station network covering a broad offshore region east of northeastern Japan. To best use the S‐net data, we estimated sensor orientations of all 150 S‐net stations, because without this information the orientations of measurements in geodetical coordinates cannot be specified. We determined three parameters of the sensor orientation at each station: the tilt angle of the long axis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…To improve earthquake early warning (EEW) for offshore earthquakes, it is important to understand the characteristics of strong motions in the offshore area. It is also crucial to examine the properties of the recorded motions at the ocean-bottom sites for various seismological and engineering applications by comparing with the data recorded by seismometers installed firmly on the ground or borehole because the waveforms at the ocean-bottom sites are likely to be contaminated by various factors such as tilting of the sensors due to strong motions and poor coupling between the sensor houses and the seabed sediments (e.g., Nakamura and Hayashimoto 2019;Takagi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To improve earthquake early warning (EEW) for offshore earthquakes, it is important to understand the characteristics of strong motions in the offshore area. It is also crucial to examine the properties of the recorded motions at the ocean-bottom sites for various seismological and engineering applications by comparing with the data recorded by seismometers installed firmly on the ground or borehole because the waveforms at the ocean-bottom sites are likely to be contaminated by various factors such as tilting of the sensors due to strong motions and poor coupling between the sensor houses and the seabed sediments (e.g., Nakamura and Hayashimoto 2019;Takagi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We use three-component 100-Hz-sampled waveforms obtained from the S-net OBSs with a natural frequency of 15 Hz. We rotate waveforms to the geographic directions (up, east, and north) based on sensor orientations 24 (see Methods). We use practically the same procedure employed by Nakajima et al…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the azimuth of the seismometers are estimated to be 3-12°2 4 . Takagi et al 24 also found that some large earthquakes resulted in the rotation of the observation pressure vessel. The M W 6.0 off-Sanriku earthquake on August 20, 2016 and the M W 6.9 off-Fukushima earthquake on November 22, 2016, caused rotation with 1 degree or more for 1 station and 3 stations, respectively.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations